Предмет: Алгебра,
автор: Taisiya2002
Раскройте скобки:
(t+m)^2
(t-3)^2
(2t+1)^2
(3m-2t)^2
(3m^2+t^3)^2
Ответы
Автор ответа:
0
здесь мы применяем формулу (a+b)²=a²+2ab+b² и (a-b)²=a²-2ab+b²
(t+m)²=t²+2tm+m²
(t-3)²=t²-6t+9
(2t+1)²=4t²+4t+1
(3m-2t)²=9m²-12mt+4t²
(3m²+t³)²=9m⁴+6m²t³+t⁶
(t+m)²=t²+2tm+m²
(t-3)²=t²-6t+9
(2t+1)²=4t²+4t+1
(3m-2t)²=9m²-12mt+4t²
(3m²+t³)²=9m⁴+6m²t³+t⁶
Похожие вопросы
Предмет: Математика,
автор: buchkovkirill
Предмет: Русский язык,
автор: robloxgirl86
Предмет: Информатика,
автор: sokolma2009
Предмет: Математика,
автор: dimas152003
Предмет: Математика,
автор: Аноним